Successful transfer of collagen-induced arthritis to severe combined immunodeficient (SCID) mice. - Williams, R O (1992)
We describe the adoptive transfer of erosive arthritis to an immunodeficient host. Spleen cells from arthritic DBA/1 mice (H-2q), immunized 4-6 weeks previously with bovine type II collagen in adjuvant, were transferred intraperitoneally into SCID mice (H-2d). SCID recipient mice also received native or denatured type II collagen (100 micrograms intraperitoneally) at the time of cell transfer. Arthritis developed in five out of five mice approximately 2 weeks after injection of cells plus native collagen, whereas animals injected with cells plus denatured collagen did not show any clinical or histological evidence of arthritis. The minimum graft size required for successful transfer of arthritis was established at 10(7) DBA/1 spleen cells. Histological examination of the joints of arthritic SCID recipient mice revealed synovitis, fibrosis and erosion of cartilage and underlying bone. Mean circulating levels of anti-type II collagen IgG were found to be significantly higher in mice injected with native collagen than those injected with denatured collagen (40 micrograms/ml and less than 1 microgram/ml, respectively). The ability to transfer collagen-induced arthritis adoptively should facilitate the study of the cellular requirement and pathological mechanisms involved in the induction of this arthropathy.